RINGA: An Identity of Bonda Women - Behera, Banita (IJRDO - Journal of Social Science and Humanities Research, 2018)
The advent of weaving and wearing natural fibre among the tribal societies has been a long history. With the intervention of developed societies and Government policies and their acculturation and assimilation with the tribal societies has resulted in replacement of natural fibre in clothing with cotton threads. This present paper is an attempt to explore the socio-cultural importance of a fibre made loincloth among the Bondas of Malkangiri district of Odisha. This paper also tries to ponder upon the social values of making process of Ringa among the Bondas. The Bonda also known as Bondo , with very few population is one of the Particularly vulnerable tribe of Odisha in the district of Malkangiri. Odisha with 62 numbers of vibrating tribal communities holds first position in India for varieties. The indigenous tribal people of Odisha along with their culturally rooted aesthetic principles and associated moral and religious values emphasize their adornment pattern, art and craft as a unique one.